PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KUBUNG KABUPATEN SOLOK - Elda, Siska; Aima, Zulfitri; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
Background of this research is a lack of student interest in learning because learning is less fun and studentâs grade VIII SMPN 1 Kubung Kabupaten Solok cemprehension of mathematical concepts still low. The purpose of this research is to know what is studentâs comprehension of mathematical concept at grade VIII SMPN 1 Kubung Kabupaten Solok by using quiz team strategy better than convensional learning. The kind of this research is experimental research, with the research plan is random on subject. The population of this researchÂ is students at grade VIII SMPN 1 Kubung Kabupaten Solok academic year 2013/2014. Tecnique of analysis data is t-test one side by using minitab. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at Î± is 0,05 and the results obtained from testing the hypothesis P-value equal to 0,001 means that Î± is smaller than 0,05. Hipothesis is accepted in thisÂ research, so that it can be concluded that studentâs comprehension of mathematical concept is treated by using quiz team strategy better than studentâs comprehension of masthematical concepts is treated by using convensional learning at grade SMPN 1 Kubung Kabupaten Solok